Crab communities (Decapoda: Brachyura) in mangrove and estuaries in the Eastern Part of Lombok Island - Dewi Citra Murniati (The East Java Biological Society, 2017)
Mangroves and estuary ecosystem in East Lombok which are appointed as Local Marine Conservation Areas (Kawasan Konservasi Laut Daerah/KKLD) are Gili Lawang, Gili Sulat, Sambelia and Jerowaru districts. Inventory of aquatic fauna in mangroves and estuaries is one of the important components of the marine conservation program. The objective of this study is to determine crab species composition in mangroves and estuaries of eastern Lombok during the East Lombok KKLD program. Targeted area for this study includes Gili Lawang, Gili Sulat in southern Lombok Island, Sugian in Sambelia, Ekas Beach, Tanjung Luar and Seriwe in Jerowaru, and Kidang in western Jerowaru. The crab was collected at 0 m to 100 m of seashore by digging the burrow. The crab community recorded was analyzed for resulting the Diversity, Evenness and Similarity Index. Ten families with 35 species of crab were found from two ecosystem types, mangrove and estuary. Each location has different diversity of ecosystem and habitat. The highest diversity is recorded in Kidang and Seriwe, while the lowest diversity in Gili Sulat. Species diversity is associated with ecosystem and habitat type diversity. Kidang and Seriwe has the highest ecosystem and habitat diversity, while Gili Sulat has the lowest diversity. In addition, the population of Ocypodidae is accounted as the dominant crab family for which Austruca perplexa is the dominant species.